2019
DOI: 10.1016/j.jconrel.2019.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Functional assessment of peptide-modified PLGA nanoparticles against oral biofilms in a murine model of periodontitis

Abstract: The interaction of the periodontal pathogen Porphyromonas gingivalis (Pg) with commensal streptococci promotes Pg colonization of the oral cavity. Previously, we demonstrated that a peptide (BAR) derived from Streptococcus gordonii (Sg) potently inhibited adherence of Pg to streptococci and reduced Pg virulence in a mouse model of periodontitis. Thus, BAR may represent a novel therapeutic to control periodontitis by preventing Pg colonization of the oral cavity. However, while BAR inhibited the initial formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 56 publications
0
56
0
Order By: Relevance
“…Collectively, the above results substantiated that LCD NP may serve as a potential nanotherapy for the treatment of both acute and chronic inflammatory diseases resulting from neutrophil and macrophage infiltration. In addition to systemic delivery, LCD NP can be administered by local injection, such as for the treatment of periodontal disease (a set of inflammatory conditions in periodontal tissues), since previous studies have demonstrated therapeutic advantages of several nanoplatforms . Also, the periodontal treatment might be beneficial for therapy of systemic inflammatory diseases such as diabetes and atherosclerosis in view of their close link with periodontal disease .…”
mentioning
confidence: 99%
“…Collectively, the above results substantiated that LCD NP may serve as a potential nanotherapy for the treatment of both acute and chronic inflammatory diseases resulting from neutrophil and macrophage infiltration. In addition to systemic delivery, LCD NP can be administered by local injection, such as for the treatment of periodontal disease (a set of inflammatory conditions in periodontal tissues), since previous studies have demonstrated therapeutic advantages of several nanoplatforms . Also, the periodontal treatment might be beneficial for therapy of systemic inflammatory diseases such as diabetes and atherosclerosis in view of their close link with periodontal disease .…”
mentioning
confidence: 99%
“…The fiber solution was subsequently vortexed, sonicated for 5 min, and dissolved for 1 h in a dark room. The quantity of extracted F-BAR was determined by measuring the fluorescence using a spectrophotometer (488/518 nm excitation/emission), relative to an F-BAR standard (Kalia et al, 2017;Mahmoud et al, 2018Mahmoud et al, , 2019. A standard curve of F-BAR was obtained by adding 0.1 mg F-BAR to 1 mL of 1:9 DMSO:TE, and serially diluting in 1:9 DMSO:TE.…”
Section: Ef Characterization: Ef Morphology Diameter Bar Loading Amentioning
confidence: 99%
“…Telomerase immortalized gingival keratinocytes (TIGKs) were grown on 12-well collagen-coated plates (Becton Dickinson, Bedford, MA) and cultured using DermaLife K Calcium Free Medium (LifeFactors R ) supplemented with penicillin/streptomycin (100 U/mL final concentration; St. Louis, MO), insulin (5 µg/mL), recombinant human (rh), L-glutamine (6 mM), apo-transferrin (5 µg/mL), epinephrine (1 µM), rh TGF-α (0.5 ng/mL), extract P TM , calcium chloride (0.06 mM) and hydrocortisone hemisuccinate (100 ng/mL). The cells were incubated at 37 • C in the presence of 5% CO 2 for 6 days until they reached 95% confluence (Mahmoud et al, 2019).…”
Section: Tissue Culturementioning
confidence: 99%
See 2 more Smart Citations